Running wild ebook A novel. - Tucker, K.A (The Simple Wild, 2022)
From the internationally bestselling author of The Simple Wild comes the story of a woman at a crossroads in her life, struggling between the safe route and the one that will only lead to more heartbreak. Veterinarian Marie Lehr knows unrequited love all too well after pining for her best friend, only to watch him marry another woman. It's a mistake she will never make again, especially not when she can practically hear the clock ticking on her childbearing years. The trouble is, she can't seem to find anyone who appeals to her even a fraction as much as that burly bush pilot did. Competitive musher Tyler Brady certainly doesn't, especially not after the heated altercation with the handsome but arrogant, spiteful man. Or so she thinks. While volunteering at the Iditarod Sled Dog Race, Marie discovers that first impressions may have been false, and her attraction to Tyler is very real. But his heart belongs to someone else, leaving him with nothing to offer but friendship. Marie's been down this road before and knows how that ends. Yet, no matter how hard she works to keep from falling for Tyler, it seems she's doomed to follow her own trail once again.